Composite solid electrolyte membrane and lithium battery

By using porous organic and inorganic composite base film, lithium conduction polymer and lithium salt in solid electrolyte membrane, combined with inorganic nanoparticles rich in lithium sulfonate groups on the surface and phase separation agent, the decomposition of traditional solid electrolyte at high voltage is solved. The problem of this paper achieves the balance of high ionic conductivity and wide electrochemical windows, and improves the stability and energy density of the battery.

CN119133579APending Publication Date: 2024-12-13SHANGHAI UNIV +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411265180.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-10
Publication Date
2024-12-13

AI Technical Summary

Technical Problem

Traditional polymer solid electrolytes are prone to irreversible oxidation and decomposition at high voltages, resulting in deterioration of interface stability, limiting the use of high voltage positive electrode materials and the increase in energy density of all solid batteries, and it is particularly difficult to take into account high ionic conductivity and wide electrochemical windows. performance.

Method used

Using porous organic and inorganic composite base film, lithium conduction polymer and lithium salt composite solid electrolyte membrane, the surface of inorganic nanoparticles and phase separation agents are enriched with lithium sulfonate groups to enhance ion conduction and oxidation stability, and broaden electricity. Chemistry window.

Benefits of technology

The ionic conductivity and electrochemical window of solid electrolytes are improved, the stability at high voltages is enhanced, and the irreversible decomposition is prevented, and a wider electrochemical window and higher energy density is achieved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119133579A_ABST
    Figure CN119133579A_ABST
Patent Text Reader

Abstract

The invention relates to a composite solid-state electrolyte membrane and a lithium battery. The composite solid-state electrolyte membrane comprises the following raw material components: a porous organic-inorganic composite base membrane, a binary lithium-conducting polymer and a lithium salt, wherein the porous organic-inorganic composite base membrane is prepared from the following raw material components: inorganic nanoparticles of which the surfaces are rich in lithium sulfonate groups, polyvinylidene fluoride-hexafluoropropylene and a phase separation agent; relative to 1 part by weight of the polyvinylidene fluoride-hexafluoropropylene, the amount of the phase separating agent is 0.1-0.5 part by weight. The composite solid electrolyte membrane provided by the invention has both high ionic conductivity and wide electrochemical window in electrochemical performance, and the interface stability of the composite solid electrolyte under high voltage is enhanced.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the technical field of lithium batteries, and in particular to a composite solid electrolyte membrane and a lithium battery. Background Art

[0002] Solid-state lithium metal batteries have attracted much attention due to their high energy density and potential for improved safety, making them the most competitive candidate to replace traditional lithium-ion batteries. As an important component of solid-state lithium metal batteries, the performance and physical parameters of solid electrolytes have a significant impact on electrochemical performance and energy density. Recent studies have shown that solid-state electrolytes combined with high-voltage cathodes can enable solid-state lithium metal batteries to achieve higher energy density.

[0003] At present, although traditional polymer solid electrolytes have advantages such as good flexibility and easy processing, they will undergo irreversible oxidative decomposition when charged and discharged at high voltage, resulting in continuous deterioration of interface stability, and ultimately rapid decay of battery capacity, which seriously limits the use of 4-5V high-voltage positive electrode materials and the improvement of all-solid-state battery energy density. Although there are currently a variety of modification methods, the preparation of a solid electrolyte with excellent electrochemical properties is still challenging, especially a solid electrolyte that takes into account both high ionic conductivity and a wide electrochemical window in electrochemical performance. Summary of the invention

[0004] The present application provides a composite solid electrolyte membrane and a lithium battery to solve the following technical problem: how to improve the electrochemical performance of the solid electrolyte.

[0005] In a first aspect, the present application provides a composite solid electrolyte membrane, wherein the raw material components of the composite solid electrolyte membrane include: a porous organic-inorganic composite base membrane, a binary lithium-conducting polymer, and a lithium salt;

[0006] The raw material components of the porous organic-inorganic composite base membrane include: inorganic nanoparticles with rich lithium sulfonate groups on the surface, polyvinylidene fluoride-hexafluoropropylene and a phase separation agent;

[0007] The phase separation agent is contained in an amount of 0.1 to 0.5 parts by weight relative to 1 part by weight of the polyvinylidene fluoride-hexafluoropropylene.

[0008] Optionally, relative to 1 part by weight of the polyvinylidene fluoride-hexafluoropropylene, the phase separation agent is 0.2 to 0.4 parts by weight.

[0009] Optionally, the phase separation agent includes at least one of the following: succinonitrile, polyethylene glycol, and carbonamide.

[0010] Optionally, relative to 1 part by weight of the polyvinylidene fluoride-hexafluoropropylene, the inorganic nanoparticles are in an amount of 0.21 parts by weight to 0.25 parts by weight.

[0011] Optionally, the inorganic nanoparticles include at least one of the following: porous silica nanoparticles and porous alumina nanoparticles.

[0012] Optionally, the binary lithium-conducting polymer is obtained by polymerizing vinyl ethylene carbonate and polyethylene glycol diacrylate.

[0013] Optionally, the lithium salt includes at least one of the following: lithium bis(trifluoromethanesulfonyl)imide, lithium bis(fluorosulfonyl)imide, difluorooxalyl borate

[0014] Optionally, the composite solid electrolyte membrane has a thickness of 1 μm to 30 μm.

[0015] Optionally, the composite solid electrolyte membrane meets the following properties: effective conductivity at room temperature is 1.2×10 -4 S cm -1 Above, the electrochemical window is greater than 5.0V.

[0016] In a second aspect, the present application provides a lithium battery, comprising the composite solid electrolyte membrane described in any one embodiment of the first aspect.

[0017] The above technical solution provided by the embodiment of the present application has the following advantages compared with the prior art:

[0018] The composite solid electrolyte membrane provided in the embodiment of the present application comprises raw material components including: a porous organic-inorganic composite base membrane, a binary lithium-conducting polymer and a lithium salt; wherein the raw material components of the porous organic-inorganic composite base membrane comprise: inorganic nanoparticles having a surface rich in lithium sulfonate groups, polyvinylidene fluoride-hexafluoropropylene and a phase separation agent; relative to 1 part by weight of the polyvinylidene fluoride-hexafluoropropylene, the phase separation agent is 0.1 to 0.5 parts by weight. The porous organic-inorganic composite substrate can provide a porous framework for the binary lithium-conducting polymer, and the inorganic nanoparticles with rich lithium sulfonate groups on the surface of the porous organic-inorganic composite substrate can provide cation exchange sites for the lithium ion conduction in the binary lithium-conducting polymer, while the lithium salt can promote the lithium ion conduction in the binary lithium-conducting polymer. Therefore, the three can synergistically enhance the ion conduction capacity of the composite solid electrolyte membrane, so that it can have a higher ion conductivity at room temperature; the inorganic nanoparticles with rich lithium sulfonate groups on the surface can cooperate with succinonitrile to enhance the oxidative stability of the binary lithium-conducting polymer components, inhibit their decomposition under high voltage, and ultimately broaden the electrochemical window of the composite solid electrolyte; the inorganic nanoparticles with rich lithium sulfonate groups on the surface can affect the ion conduction structure in the binary lithium-conducting polymer, greatly improve the ion conductivity of the composite solid electrolyte, and inhibit the movement of anions, preventing the irreversible decomposition of the polymer under high voltage to obtain a wider electrochemical window; the fluorine-containing and -CF3 groups in polyvinylidene fluoride-hexafluoropropylene The stability of the composite solid electrolyte under high voltage can be greatly improved; the phase separation agent can make the organic-inorganic composite base film obtain a more uniform porous structure, and can use its own functional groups to affect the lithium ion conduction in the polymer, reduce the lithium ion conduction barrier, thereby improving the conductivity of the composite solid electrolyte, and can enhance the oxidation stability of the polymer, and finally improve the electrochemical window of the solid electrolyte; thus, the inorganic nanoparticles rich in lithium sulfonate groups on the surface and the phase separation agent synergistically promote the dissociation of lithium salts through their own functional groups, and affect the lithium ion transport structure in the polymer, reducing the lithium ion transport barrier; at the same time, the two synergistically enhance the oxidation stability of the composite solid electrolyte, inhibit its irreversible decomposition under high voltage, and finally obtain a wider electrochemical window; at the same time, polyvinylidene fluoride-hexafluoropropylene itself has high electrochemical stability, which provides a good electrochemical window foundation for the composite solid electrolyte, and synergistically promotes the stability of the polymer after being composited with the phase separation agent and the inorganic nanoparticles rich in lithium sulfonate groups on the surface. In summary, the electrochemical performance of the solid electrolyte is improved. BRIEF DESCRIPTION OF THE DRAWINGS

[0019] The accompanying drawings, which are incorporated in and constitute a part of this specification, illustrate embodiments consistent with the present application and, together with the description, serve to explain the principles of the present application.

[0020] In order to more clearly illustrate the embodiments of the present application or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, for ordinary technicians in this field, other drawings can be obtained based on these drawings without paying any creative labor.

[0021] Figure 1 This is a scanning electron microscope image of a composite solid electrolyte membrane provided in Example 1 of the present application;

[0022] Figure 2 A scanning electron microscope image of a composite solid electrolyte membrane provided in Comparative Example 3 of the present application;

[0023] Figure 3 A comparison chart of ionic conductivity and migration number of a composite solid electrolyte membrane provided in an embodiment of the present application;

[0024] Figure 4 A high voltage battery cycle test diagram of a composite solid electrolyte membrane provided in an embodiment of the present application;

[0025] Figure 5 A graph showing the cycling stability of a lithium symmetric battery of a composite solid electrolyte membrane provided in an embodiment of the present application;

[0026] Figure 6 This is an electrochemical window test diagram of a composite solid electrolyte membrane provided in an embodiment of the present application. DETAILED DESCRIPTION

[0027] In order to make the purpose, technical solution and advantages of the embodiments of the present application clearer, the technical solution in the embodiments of the present application will be clearly and completely described below in conjunction with the drawings in the embodiments of the present application. Obviously, the described embodiments are part of the embodiments of the present application, not all of the embodiments. Based on the embodiments in the present application, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of this application.

[0028] Various embodiments of the present application may be presented in the form of a range; it should be understood that the description in the form of a range is only for convenience and brevity, and should not be understood as a rigid limitation on the scope of the present application; therefore, the range description should be considered to have specifically disclosed all possible sub-ranges and single numerical values ​​within the range. For example, the range description from 1 to 6 should be considered to have specifically disclosed sub-ranges, such as from 1 to 3, from 1 to 4, from 1 to 5, from 2 to 4, from 2 to 6, from 3 to 6, etc., as well as single numbers within the range, such as 1, 2, 3, 4, 5 and 6, which apply regardless of the range. In addition, whenever a numerical range is indicated herein, it is meant to include any cited number (fractional or integer) within the indicated range.

[0029] In the present application, in the description of the specification of the present application, the terms "including", "comprising", etc. mean "including but not limited to". In this article, "at least one" means one or more, and "plurality" means two or more. "At least one", "at least one of the following" or similar expressions refer to any combination of these items, including any combination of single items or plural items. For example, "at least one of a, b, or c", or "at least one of a, b, and c" can all mean: a, b, c, ab (i.e., a and b), ac, bc, or abc, where a, b, c can be single or multiple, respectively.

[0030] Unless otherwise specified, various raw materials, reagents, instruments and equipment used in this application can be purchased from the market or prepared by existing methods.

[0031] In a first aspect, the present application provides a composite solid electrolyte membrane, wherein the raw material components of the composite solid electrolyte membrane include: a porous organic-inorganic composite base membrane, a binary lithium-conducting polymer, and a lithium salt;

[0032] The raw material components of the porous organic-inorganic composite base membrane include: inorganic nanoparticles with rich lithium sulfonate groups on the surface, polyvinylidene fluoride-hexafluoropropylene and a phase separation agent;

[0033] The phase separation agent is contained in an amount of 0.1 to 0.5 parts by weight relative to 1 part by weight of the polyvinylidene fluoride-hexafluoropropylene.

[0034] In the embodiment of the present application, the porous organic-inorganic composite base membrane can provide a porous framework for the binary lithium-conducting polymer, and the inorganic nanoparticles rich in lithium sulfonate groups on the surface of the porous organic-inorganic composite base membrane can provide cation exchange sites for lithium ion conduction in the binary lithium-conducting polymer, and the lithium salt can promote the lithium ion conduction in the binary lithium-conducting polymer, so that the three can synergistically enhance the ion conduction capacity of the composite solid electrolyte membrane, so that it can have a higher ion conductivity at room temperature; the inorganic nanoparticles rich in lithium sulfonate groups on the surface can cooperate with succinonitrile to enhance the oxidative stability of the binary lithium-conducting polymer components, inhibit their decomposition under high voltage, and ultimately broaden the electrochemical window of the composite solid electrolyte; the inorganic nanoparticles rich in lithium sulfonate groups on the surface can affect the ion conduction structure in the binary lithium-conducting polymer, greatly improve the ionic conductivity of the composite solid electrolyte, and inhibit the movement of anions, prevent the irreversible decomposition of the polymer under high voltage, so that it obtains a wider electrochemical window; polyvinylidene fluoride-hexafluoropropylene has good plasticity, can provide good support for the polymer, and can make the composite solid electrolyte The electrolyte has stronger mechanical properties and thermal stability, and the fluorine and -CF3 groups therein can greatly improve the stability of the composite solid electrolyte under high voltage; the phase separation agent can make the organic-inorganic composite base membrane obtain a more uniform porous structure, and can use its own functional groups to affect the lithium ion conduction in the polymer, reduce the lithium ion conduction barrier, and improve the conductivity of the composite solid electrolyte, and can enhance the oxidation stability of the polymer, and ultimately improve the electrochemical window of the solid electrolyte; thus, the inorganic nanoparticles rich in lithium sulfonate groups on the surface and the phase separation agent synergistically promote the dissociation of lithium salts through their own functional groups, and affect the lithium ion transport structure in the polymer, reducing the lithium ion transport barrier; at the same time, the two synergistically enhance the oxidation stability of the composite solid electrolyte, inhibit its irreversible decomposition under high voltage, and ultimately obtain a wider electrochemical window; at the same time, polyvinylidene fluoride-hexafluoropropylene itself has high electrochemical stability, which provides a good electrochemical window basis for the composite solid electrolyte, and synergistically promotes the stability of the polymer after being composited with the phase separation agent and the inorganic nanoparticles rich in lithium sulfonate groups on the surface.

[0035] In some embodiments, the phase separation agent is in an amount of 0.2 to 0.4 parts by weight relative to 1 part by weight of the polyvinylidene fluoride-hexafluoropropylene.

[0036] In the embodiments of the present application, the phase separation agent is limited to 0.1 to 0.5 parts by weight relative to 1 part by weight of polyvinylidene fluoride-hexafluoropropylene. The reason is that: the organic-inorganic composite base film can form a uniform porous structure, accelerate the transmission of lithium ions in the binary lithium-conducting polymer, and broaden the electrochemical window. At the same time, the phase separation agent and inorganic nanoparticles synergistically promote the stability of the polymer under high voltage. Exemplarily, relative to 1 part by weight of polyvinylidene fluoride-hexafluoropropylene, the phase separation agent can be 0.1 parts by weight, 0.2 parts by weight, 0.3 parts by weight, 0.4 parts by weight, 0.5 parts by weight, etc., and further, relative to 1 part by weight of polyvinylidene fluoride-hexafluoropropylene, the phase separation agent can be 0.2 parts by weight, 0.3 parts by weight, 0.4 parts by weight, etc.

[0037] In some embodiments, the phase separation agent includes at least one of the following: succinonitrile, polyethylene glycol, and carbonamide.

[0038] In the embodiments of the present application, the phase separation agent can be selected from one or more of succinonitrile, polyethylene glycol, and carbonamide, which can produce a uniform porous organic-inorganic composite base membrane, laying the foundation for the composite of the polymer and it.

[0039] In some embodiments, the inorganic nanoparticles are present in an amount of 0.21 to 0.25 parts by weight relative to 1 part by weight of the polyvinylidene fluoride-hexafluoropropylene.

[0040] In the embodiment of the present application, the inorganic nanoparticles are limited to 0.21 to 0.25 parts by weight relative to 1 part by weight of polyvinylidene fluoride-hexafluoropropylene, and the surface groups of the inorganic particles can be fully utilized to affect the dissociation of lithium salts in the polymer and the conduction of lithium ions, thereby improving the final electrochemical performance of the solid electrolyte. Exemplarily, for 1 part by weight of polyvinylidene fluoride-hexafluoropropylene, the inorganic nanoparticles can be 0.21 parts by weight, 0.22 parts by weight, 0.23 parts by weight, 0.24 parts by weight, 0.25 parts by weight, etc.

[0041] In some embodiments, the inorganic nanoparticles include at least one of the following: porous silica nanoparticles, porous alumina nanoparticles.

[0042] In the embodiments of the present application, the inorganic nanoparticles may be selected from one or more of porous silica nanoparticles and porous alumina nanoparticles.

[0043] In some embodiments, the binary lithium-conducting polymer is obtained by polymerizing vinyl ethylene carbonate and polyethylene glycol diacrylate.

[0044] In the embodiments of the present application, vinyl ethylene carbonate (VEC) and polyethylene glycol diacrylate (PEGDA) are double-bond polymerized by a photoinitiator to form a binary lithium-conducting polymer, and the ether-ester cross-linked synergistic structure greatly improves the conductivity of lithium ions in the polymer.

[0045] In some embodiments, the lithium salt includes at least one of the following: lithium bis(trifluoromethanesulfonyl)imide, lithium bis(fluorosulfonyl)imide, and difluorooxalatoboric acid.

[0046] In the embodiment of the present application, the lithium salt can be selected from one or more of lithium bis(trifluoromethanesulfonyl)imide, lithium bis(fluorosulfonyl)imide, and difluorooxalatoboric acid as inorganic nanoparticles. Furthermore, binary lithium salts can be selected, which can not only improve ion conduction, but also promote the formation of a stable SEI layer rich in inorganic components, which is beneficial to the stability of the battery over a long cycle.

[0047] In some embodiments, the composite solid electrolyte membrane has a thickness of 1 μm to 30 μm.

[0048] In some embodiments, the composite solid electrolyte membrane meets the following properties: effective conductivity at room temperature is 1.2x10 -4 S.cm -1 Above, the electrochemical window is greater than 5.0 V, and the effective conductivity at room temperature represents the product of the conductivity at room temperature and the migration number.

[0049] In the embodiment of the present application, the composite solid electrolyte membrane can match the high nickel ternary positive electrode material and has a high initial capacity and cycle retention rate. The composite solid electrolyte membrane has a thin thickness and excellent electrochemical performance, which is specifically reflected in high ionic conductivity and a wide electrochemical window.

[0050] The preparation method of the inorganic nanoparticles rich in lithium sulfonate groups comprises: a. dispersing the nanoparticles with surface grafted sulfonic acid groups in water, and then dropping a lithium-containing alkaline solution until the solution is neutral. b. stirring fully at a certain temperature, evaporating and removing the solvent, and then vacuum drying to obtain inorganic nanoparticles rich in lithium sulfonate groups. Wherein, the lithium-containing alkaline solution can be a lithium hydroxide aqueous solution or a lithium carbonate aqueous solution, and the stirring temperature can be 60-80°C. Exemplarily, the sulfonated nanoparticles Al2O3-SO3H are dispersed in water. Use 0.1wt% lithium hydroxide solution to titrate the aqueous solution dispersed with Al2O3-SO3Li to pH 7, then stir at 80°C for 12 hours, stir the solvent to dry, and then vacuum dry at 80°C to obtain inorganic nanoparticles Al2O3-SO3Li powder rich in lithium sulfonate groups.

[0051] The method for preparing the composite solid electrolyte membrane comprises:

[0052] S1, obtaining inorganic nanoparticles with a surface rich in lithium sulfonate groups;

[0053] S2, mixing the inorganic nanoparticles, polyvinylidene fluoride-hexafluoropropylene, a phase separation agent and a solvent to obtain a mixed solution;

[0054] S3, applying the mixed solution on the surface of the substrate, and then vacuum drying to obtain a porous organic-inorganic composite base film;

[0055] S4, mixing the lithium salt, the photoinitiator and the monomer to obtain a precursor solution;

[0056] S5, immersing the porous organic-inorganic composite base membrane in the precursor solution, and then curing it to obtain a composite solid electrolyte membrane; wherein, in step S2, the solvent is a mixed solution of N,N-dimethylformamide, dimethyl sulfoxide, N-methylpyrrolidone, acetone and water, and the substrate is aluminum foil, stainless steel plate or glass plate;

[0057] The monomers are polyethylene glycol diacrylate and vinyl ethylene carbonate; polyethylene glycol diacrylate / vinyl ethylene carbonate is 0-20wt%; two lithium salts are used, and the concentrations are 1-2mol / L and 0.1-0.5mol / L respectively; the photoinitiator is 0.5-5% of the total mass of polyethylene glycol diacrylate and vinyl ethylene carbonate; the photoinitiator is 2-hydroxy-2-methyl-1-phenylacetone; the immersion time is 0-24 hours; and the curing is achieved by the wavelength of the ultraviolet lamp being 365nm and the irradiation time being 1min-10min. Exemplarily, a certain ratio of polyvinylidene fluoride-hexafluoropropylene, Al2O3-SO3Li and succinonitrile are stirred in a mixed solvent of water and acetone, coated on aluminum foil, and vacuum dried at 80°C to obtain a polyvinylidene fluoride-hexafluoropropylene / Al2O3-SO3Li base film. The specific ratio is: Al2O3-SO3Li is 21wt% of polyvinylidene fluoride-hexafluoropropylene, and succinonitrile is 30wt% of polyvinylidene fluoride-hexafluoropropylene; a certain ratio of vinyl ethylene carbonate, polyethylene glycol diacrylate, lithium bistrifluoromethanesulfonamide, lithium difluorooxalatoborate and 2-hydroxy-2-methyl-1-phenylacetone are mixed and stirred to obtain a precursor solution. The specific ratio is: polyethylene glycol diacrylate / ethylene carbonate is 15wt%, the concentration of lithium bistrifluoromethanesulfonamide is 1mol / L, the concentration of lithium difluorooxalatoborate is 0.1mol / L, and 2-hydroxy-2-methyl-1-phenylacetone is 0.5wt% of the polyethylene glycol diacrylate and vinyl carbonate solution; polyvinylidene fluoride-hexafluoropropylene / Al2O3-SO3Li is immersed in the precursor solution for 1 hour; the immersed film is placed under an ultraviolet lamp (365nm) for 2 minutes for curing to obtain a composite solid electrolyte membrane.

[0058] In a second aspect, the present application provides a lithium battery, comprising the composite solid electrolyte membrane described in any one embodiment of the first aspect.

[0059] In the embodiments of the present application, the composite solid electrolyte membrane has a thin thickness and high room temperature conductivity and lithium ion transference number in the preparation of a high voltage all-solid-state lithium metal battery.

[0060] The lithium battery is realized based on the above-mentioned composite solid electrolyte membrane. The specific components of the composite solid electrolyte membrane can refer to the above-mentioned embodiments. Since the lithium battery adopts part or all of the technical solutions of the above-mentioned embodiments, it has at least all the beneficial effects brought by the technical solutions of the above-mentioned embodiments, which will not be described one by one here.

[0061] The present application will be further described below in conjunction with specific embodiments. It should be understood that these embodiments are intended only to illustrate the present application and are not intended to limit the scope of the present application. The experimental methods for which specific conditions are not specified in the following examples are usually measured according to national standards. If there is no corresponding national standard, then the conditions recommended by the manufacturer are followed.

[0062] Example 1

[0063] A composite solid electrolyte membrane, the raw material components of the composite solid electrolyte membrane include: a porous organic-inorganic composite base membrane, a binary lithium-conducting polymer, and lithium bis(trifluoromethanesulfonic acid)imide and lithium difluorooxalate borate;

[0064] The raw materials of the porous organic-inorganic composite base membrane include: Al2O3-SO3Li particles, polyvinylidene fluoride-hexafluoropropylene and succinonitrile;

[0065] The amount of the phase separation agent was 0.3 parts by weight relative to 1 part by weight of the polyvinylidene fluoride-hexafluoropropylene.

[0066] The amount of the inorganic nanoparticles was 0.21 parts by weight relative to 1 part by weight of the polyvinylidene fluoride-hexafluoropropylene.

[0067] The binary lithium-conducting polymer is obtained by polymerization of vinyl ethylene carbonate and polyethylene glycol diacrylate.

[0068] Example 2

[0069] A composite solid electrolyte membrane, the raw material components of the composite solid electrolyte membrane include: a porous organic-inorganic composite base membrane, a binary lithium-conducting polymer, and lithium bis(trifluoromethanesulfonic acid)imide and lithium difluorooxalate borate;

[0070] The raw materials of the porous organic-inorganic composite base membrane include: Al2O3-SO3Li particles, polyvinylidene fluoride-hexafluoropropylene and succinonitrile;

[0071] The amount of the phase separation agent was 0.2 parts by weight relative to 1 part by weight of the polyvinylidene fluoride-hexafluoropropylene.

[0072] The amount of the inorganic nanoparticles was 0.21 parts by weight relative to 1 part by weight of the polyvinylidene fluoride-hexafluoropropylene.

[0073] The binary lithium-conducting polymer is obtained by polymerization of vinyl ethylene carbonate and polyethylene glycol diacrylate.

[0074] Example 3

[0075] A composite solid electrolyte membrane, the raw material components of the composite solid electrolyte membrane include: a porous organic-inorganic composite base membrane, a binary lithium-conducting polymer, and lithium bis(trifluoromethanesulfonic acid)imide and lithium difluorooxalate borate;

[0076] The raw materials of the porous organic-inorganic composite base membrane include: Al2O3-SO3Li particles, polyvinylidene fluoride-hexafluoropropylene and succinonitrile;

[0077] The amount of the phase separation agent was 0.4 parts by weight relative to 1 part by weight of the polyvinylidene fluoride-hexafluoropropylene.

[0078] The amount of the inorganic nanoparticles was 0.21 parts by weight relative to 1 part by weight of the polyvinylidene fluoride-hexafluoropropylene.

[0079] The binary lithium-conducting polymer is obtained by polymerization of vinyl ethylene carbonate and polyethylene glycol diacrylate.

[0080] Comparative Example 1

[0081] The difference from Example 1 is that Al2O3 replaces Al2O3-SO3Li particles.

[0082] Comparative Example 2

[0083] The difference from Example 1 is that the amount of Al2O3-SO3Li particles is 0.18 parts by weight relative to 1 part by weight of polyvinylidene fluoride-hexafluoropropylene.

[0084] Comparative Example 3

[0085] The difference from Example 1 is that no phase separation agent is introduced.

[0086] Comparative Example 4

[0087] The difference from Example 1 is that the amount of the phase separation agent is 0.05 parts by weight relative to 1 part by weight of polyvinylidene fluoride-hexafluoropropylene.

[0088] The performance tests were conducted on the composite solid electrolyte membranes of Examples 1 to 3 and Comparative Examples 1 to 4. Please refer to Table 1 for the results.

[0089] Table 1 Properties of composite solid electrolyte membrane

[0090]

[0091]

[0092] As can be seen from Table 1, the composite solid electrolyte membrane provided in the present application takes into account both high ionic conductivity and wide electrochemical window in electrochemical performance, and enhances the interface stability of the composite solid electrolyte at high voltage.

[0093] Figure 1 This is a scanning electron microscope image of a composite solid electrolyte membrane provided in Example 1 of the present application; Figure 2 This is a scanning electron microscope image of a composite solid electrolyte membrane provided in Comparative Example 3 of this application; see Figures 1-2 , indicating that the composite solid electrolyte membrane in Example 1 presents a uniform porous structure, while the pore size in the composite solid electrolyte membrane in Comparative Example 3 is small and unevenly distributed. Figure 3 This is a comparison chart of ionic conductivity and migration number of a composite solid electrolyte membrane provided in an embodiment of the present application; please refer to Figure 3 , indicating that Example 1 has the best lithium ion transport performance; Figure 4 This is a high voltage battery cycle test diagram of a composite solid electrolyte membrane provided in an embodiment of the present application; please refer to Figure 4 , indicating that Example 1 has the highest initial capacity and excellent cycle retention rate; Figure 5 This is a test diagram of the cycle stability of a lithium symmetric battery of a composite solid electrolyte membrane provided in an embodiment of the present application; see Figure 5 , indicating that Example 1 has excellent lithium negative electrode interface stability; Figure 6 This is an electrochemical window test diagram of a composite solid electrolyte membrane provided in an embodiment of the present application; see Figure 6 , indicating that Example 1 has a wider electrochemical window.

[0094] The above description is only a specific implementation of the present application, so that those skilled in the art can understand or implement the present application. Various modifications to these embodiments will be apparent to those skilled in the art, and the general principles defined herein can be implemented in other embodiments without departing from the spirit or scope of the present application. Therefore, the present application will not be limited to the embodiments shown herein, but will conform to the widest range consistent with the principles and novel features applied for herein.

Claims

1. A composite solid electrolyte membrane, characterized in that: The raw material components of the composite solid electrolyte membrane include: a porous organic-inorganic composite base membrane, a binary lithium-conducting polymer and a lithium salt; The raw material components of the porous organic-inorganic composite base membrane include: inorganic nanoparticles with rich lithium sulfonate groups on the surface, polyvinylidene fluoride-hexafluoropropylene and a phase separation agent; The phase separation agent is contained in an amount of 0.1 to 0.5 parts by weight relative to 1 part by weight of the polyvinylidene fluoride-hexafluoropropylene.

2. The composite solid electrolyte membrane according to claim 1, characterized in that: The phase separation agent is contained in an amount of 0.2 to 0.4 parts by weight relative to 1 part by weight of the polyvinylidene fluoride-hexafluoropropylene.

3. The composite solid electrolyte membrane according to claim 1, characterized in that: The phase separation agent includes at least one of the following: succinonitrile, polyethylene glycol, and carbonamide.

4. The composite solid electrolyte membrane according to claim 1, characterized in that: The inorganic nanoparticles are present in an amount of 0.21 to 0.25 parts by weight relative to 1 part by weight of the polyvinylidene fluoride-hexafluoropropylene.

5. The composite solid electrolyte membrane according to claim 1, characterized in that: The inorganic nanoparticles include at least one of the following: porous silicon dioxide nanoparticles and porous aluminum oxide nanoparticles.

6. The method according to claim 1, characterized in that The binary lithium-conducting polymer is obtained by polymerizing vinyl ethylene carbonate and polyethylene glycol diacrylate.

7. The method according to claim 1, characterized in that The lithium salt includes at least one of the following: lithium bis(trifluoromethanesulfonyl)imide, lithium bis(fluorosulfonyl)imide, and lithium difluorooxalatoborate.

8. The composite solid electrolyte membrane according to claim 1, characterized in that: The thickness of the composite solid electrolyte membrane is 1 μm to 30 μm.

9. The composite solid electrolyte membrane according to any one of claims 1 to 8, characterized in that: The composite solid electrolyte membrane meets the following properties: effective conductivity at room temperature is 1.2×10 -4 S cm -1 Above, the electrochemical window is greater than 5.0V.

10. A lithium battery, characterized in that: The lithium battery comprises the composite solid electrolyte membrane according to any one of claims 1 to 9.